Integrative Analysis of Clinical Features and Cerebrospinal Fluid Immune Microenvironment in Leptomeningeal Metastasis From Non-small-cell Lung Cancer Patients. - Chen, Junjun; Zhou, Qihao; Yin, Yuan; Qin, Zhiquan; Chen, Yun (Clinical Medicine Insights: Oncology, 2026)
Background: Leptomeningeal metastasis (LM) represents one of the most severe complications in advanced lung cancer, indicating a poor prognosis. However, the mechanisms underlying LM progression remain incompletely understood, and reliable biomarkers for monitoring disease progression and treatment response are lacking. Methods: This retrospective observational study was conducted at the Zhejiang Provincial People's Hospital. Cerebrospinal fluid (CSF) samples from 13 patients with non–small cell lung cancer (NSCLC) and LM were analyzed, including biochemical parameters, tumor markers, differential cell counts, and T-cell subsets assessed by flow cytometry. Results: The median overall survival (mOS) after LM diagnosis was 15 months. During LM progression, increased CSF levels of albumin, lactate dehydrogenase (LDH), lactic acid, and carcinoembryonic antigen (CEA) were observed, accompanied by decreased glucose, chloride, lymphocyte proportion, and CD8+ T-cell proportion. In some cases, lymphocyte percentages and CD8+ T-cell proportions increased during subsequent evaluations following treatment adjustment. Conclusions: These findings suggest that CSF biochemical and immune parameters may be associated with disease progression in LM. Dynamic changes in CD8+ T-cell proportions may also reflect alterations in the CSF immune microenvironment and could represent potential targets for future immunotherapeutic strategies.